Members of German Federal Parliament more risk-loving than general population - Moritz Heß; Christian von Scheve; Jürgen Schupp; Gert G. Wagner (Deutsches Institut für Wirtschaftsforschung (DIW), 2013)
The article analyzes the question of whether career politicians differ systematically from the general population in terms of their attitudes toward risk. A written survey of members of the 17th German Bundestag in late 2011 identified their risk attitudes, and the survey data was set in relation to respondents to the German Socio-Economic Panel Study (SOEP) for the survey year 2009 (2002 through 2012). Compared with the population surveyed in the SOEP, members of the German parliament display a considerably higher general risk appe-tite, which is highly significant. For different areas of risk, last surveyed in the SOEP in 2009, the members of parliament had significantly stronger risk-loving attitudes across vir-tually all indicators and risk categories surveyed than the comparison groups of SOEP re-spondents.
Keywords: D71; D78; H11; H70; P16; Z13; 330; political decision-making; risk aversion; German parliament; SOEP